Implementasi Teknologi GPON Berbasis FTTH pada Perumahan Permata Anggrek - I Gede Agus Aditya Putra; Komang Oka Saputra; Ni Made Ary Esta Dewi Wirastuti (CV. Ulil Albab Corp, 2022)
This research was conducted by designing a Gigabit Passive Optical Network (GPON) technology based on Fiber to the Home (FTTH) using the power link budget and the resulting attenuation parameters. This research was conducted due to the alleged lack of stability of the internet network. Research is carried out scientifically so that valid data is obtained with the aim of being able to find, manage, and prove certain knowledge. The results of the study obtained that the error value contained in each comparison of the total attenuation can be said to be stable because the error value is not more than 1%